2021
DOI: 10.3390/su13105523
|View full text |Cite
|
Sign up to set email alerts
|

Public Intentions to Purchase Electric Vehicles in Pakistan

Abstract: Electric vehicles (EVs) have the potential to lead the transition in road transportation from traditional petroleum mobility to electric mobility. Despite many environmental benefits, the market penetration rate of EVs is still low in most developing countries. Recently, Pakistan formulated its first EV policy for 2020–2025 to accelerate EV adoption. This study aims to explore the factors, including environmental concerns, perceived ease of use, effort expectancy, social influence, and perceived facilitating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 52 publications
(155 reference statements)
7
39
0
6
Order By: Relevance
“…This indicates that consumers who have great social influence will have a high attitude towards electric two-wheelers. A previous study conducted by Lee et al (2021) in Pakistan did not correlate with buying EVs. Still, the present study on E2W shows positive correlations with attitudes in India.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…This indicates that consumers who have great social influence will have a high attitude towards electric two-wheelers. A previous study conducted by Lee et al (2021) in Pakistan did not correlate with buying EVs. Still, the present study on E2W shows positive correlations with attitudes in India.…”
Section: Resultsmentioning
confidence: 61%
“…They will avoid buying products for which they think there is no social approval. Previous studies' findings show that social influence is an important factor that affects consumers' intention to buy electric vehicles [49]. Tu and Yang's (2019) research showed that subjective norms significantly impact EV purchase decisions [41].…”
Section: Social Influencementioning
confidence: 99%
“…We recommend future research to address the mechanisms behind the gender differences in the acceptance of conditionally automated cars. In the study of [57], Females with higher environmental concerns were more likely than Males to intend to use automated cars. Females who considered automated cars less useful were less likely to intend to use automated cars.…”
Section: Age and Gendermentioning
confidence: 95%
“…ird, respondents from lower-GDP countries may be more comfortable with and enthusiastic about new technologies [51], probably because they are less concerned or simply less aware of so-called "higher-order needs" [55] (e.g., cybersecurity, liability, and privacy), which some see threatened by the introduction of automated cars (see [56]). Fourth, these respondents may also be more aware of governmental support and policies to enable a large-scale deployment of automated cars (see [57]). Fifth, the scepticism of higher-GDP countries representing the "classical automobile nations" such as Germany, Italy, France, and Sweden may be rooted in the expected loss of driving enjoyment due to more automation and connectivity in passenger cars.…”
Section: Differences Between Countriesmentioning
confidence: 99%
“…The effects of the perceived threat from COVID-19 on the behavioral intentions to use public transportation in the post-pandemic world were analyzed using structural equation modeling (SEM). A partial least square path modeling (PLSPM) approach of SEM was employed to capture the relationship among variables (latent constructs), consistent with previous studies [36,49,50]. It includes two models, i.e., the measurement model and the structural model.…”
Section: Structural Equation Modeling For Objectivementioning
confidence: 99%